IMPLEMENTATION OF THE PAIKEM MODEL AS AN EFFORT TO INCREASE MATHEMATICS LEARNING MOTIVATION OF CLASS V STUDENTS AT SDN 104196 TANDAM HULU - Afni, Ria; Hariati, Emy; Harahap, Syarifah Ainun (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2024)
This study aims to examine the effectiveness of implementing the PAIKEM learning model (Active, Innovative, Creative, Effective, and Enjoyable Learning) in enhancing the learning motivation of fifth-grade mathematics students at SDN 104196 Tandam Hulu, Hamparan Perak District. The research employs a correlational quantitative design, with data collected through questionnaires and documentation. The findings indicate that the application of the PAIKEM model significantly contributes to the increase in student motivation, with an average motivation improvement of over 70% and a positive correlation of 89% between the model's implementation and the enhancement of motivation (Murjiman, 2007; Sugiyono, 2012). These results suggest that a learning approach emphasizing active participation and an enjoyable classroom environment can effectively overcome the monotony of conventional teaching methods. The practical implication of this study is the necessity for teachers to adopt innovative learning models to create interactive and supportive learning environments.